HALYCH IN THE ARPAD DYNASTY POLICY (THE FRAGMENT OF THE AUTHOR’S ARTICLE) - FONT, Marta (Halych. Scientific work collection, 2015)
In the fragment of the article, the author showed the periods of the opposition between the Arpad royal dynasty of Hungary, and Princes from Kyiv and Volyn for the right to control Halych and the Halych land. The diplomacy and the war were the main ways of the goal achievement, and all the hostile parties used them successfully.